Choroidal thickness in relation to sex, age, refractive error, and axial length in healthy Turkish subjects - Tuncer, Ibrahim; Karahan, Eyyup; Zengin, Mehmet Ozgur; Atalay, Eray; Polat, Nihat (International ophthalmology, 2015)
The aim of this study was to investigate the association between choroidal thickness (CT) and sex, age, refractive error (RE), and axial length in healthy subjects. This is a study of 154 eyes in 154 healthy subjects. CT measurements were performed by the same experienced technician using a spectral domain optical coherence tomography device. CT was measured perpendicularly from the outer edge of the retinal pigment epithelium to the choroid–sclera boundary at the fovea and at six more points which are located at, respectively, 500 µm nasal to the fovea, 1,000 µm nasal to the fovea, and 1,500 μm nasal to the fovea, 500 μm temporal to the fovea, 1,000 μm temporal to the fovea, and 1,500 μm temporal to the fovea. The RE was measured by autorefractometry, and the axial length was measured by interferometry. Statistical analysis was performed to evaluate CT at each location, and to the correlations of CT with sex, age, RE, and axial length. The mean subfoveal CT was 265.86 ± 60.32 µm, the mean age was 49.01 ± 19.19 years, the mean RE was −0.17 ± 1.20 diopters (D), and the mean axial length was 23.39 ± 0.76 mm. CT profile indicated that the choroid was thicker at the fovea than at temporal and nasal locations. Univariable linear regression analysis showed that subfoveal CT decreased 3.14 µm for each year of age and decreased 79.33 µm for each mm of axial length ( P = 0.000, R 2 = 0.249; P = 0.000, R 2 = 0.487, respectively). In a similar analysis, subfoveal CT was found to decrease by 50.24 µm/D myopia-shifted change in refraction ( P = 0.000, R 2 = 0.201). The subfoveal choroid was 99.16 µm (39.22 %) thicker in men than women when adjusting for age and axial length ( P = 0.000, R 2 = 0.249). CT decreases with increasing myopia, age, and axial length. Men had thicker choroid than women, and CT varies depending on location.